Adversity Interpreted: A Scoping Review of Adversity Appraisal Measurement. (October 2022) - Gusler, Stephanie; Guler, Jessy; Petrie, Rachel; Marshall, Heather; Cooley, Daryl; Jackson, Yo
Although evidence suggests that individuals' appraisals (i.e., subjective interpretations) of adverse or traumatic life events may serve as a mechanism accounting for differences in adversity exposure and psychological adjustment, understanding this mechanism is contingent on our ability to reliably and consistently measure appraisals. However, measures have varied widely between studies, making conclusions about how best to measure appraisal a challenge for the field. To address this issue, the present study reviewed 88 articles from three research databases, assessing adults' appraisals of adversity. To be included in the scoping review, articles had to meet the following criteria: (1) published no earlier than 1999, (2) available in English, (3) published as a primary source manuscript, and (4) included a measure assessing for adults' (over the age of 18) subjective primary and/or secondary interpretations of adversity. Each article was thoroughly reviewed and coded based on the following information: study demographics, appraisal measurement tool(s), category of appraisal, appraisal dimensions (e.g., self-blame, impact, and threat), and the tool's reliability and validity. Further, information was coded according to the type of adversity appraised, the time in which the appraised event occurred, and which outcomes were assessed in relation to appraisal. Results highlight the importance of continued examination of adversity appraisals and reveal which appraisal tools, categories, and dimensions are most commonly assessed for. These results provide guidance to researchers in how to examine adversity appraisals and what gaps among the measurement of adversity appraisal which need to be addressed in the future research.